2019
DOI: 10.5812/ijhrba.86887
|View full text |Cite
|
Sign up to set email alerts
|

Trichomoniasis Prevalence at a Care Center Among Women with High-Risk Behaviors in Zahedan, Iran

Abstract: Background: Trichomoniasis is a sexually transmitted infection (STI) attributed to Trichomonas vaginalis, an anaerobic, flagellated protozoan parasite. Although trichomonacidal drugs effectively kill Trichomonas, the infection rate is still high. Objectives: The aim of the present study was to investigate the frequency of T. vaginalis among women with high-risk behaviors in Zahedan, Southeast Iran. Patients and Methods: In total, 90 symptomatic women, aged 20 to 60 years, were recruited between February and Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…In present study 48 were positive by papanicolauo staining were examined via PCR and surprisingly, molecular ampli cation did not detect more T. vaginalis cases than the papanicolauo staining and showed that 4 samples related to T. vaginalis. The result reported in our studywas in line with Haghighi et al study conducted in Zahedan, Iran and it was expected that the molecular method would produce better results; however, it should be attributed to the low amount ampli cation of DNA for visualization [10].Trichomonas prevalence varies in difference studies, which might be due to different factors, such as socio-demographic characteristics and personal hygiene [30].Current study was conducted in Tabriz, the largest city in northwest of Iran. According to ZiaeiHezarjaribiet al systematic review and meta-analysis study, trichomoniasis is more common in Central provinces of Iran and the minimum rate belongs to the eastern provinces and the mean prevalence rate in other geographical regions was 6.9, 6.7% in West, North respectively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In present study 48 were positive by papanicolauo staining were examined via PCR and surprisingly, molecular ampli cation did not detect more T. vaginalis cases than the papanicolauo staining and showed that 4 samples related to T. vaginalis. The result reported in our studywas in line with Haghighi et al study conducted in Zahedan, Iran and it was expected that the molecular method would produce better results; however, it should be attributed to the low amount ampli cation of DNA for visualization [10].Trichomonas prevalence varies in difference studies, which might be due to different factors, such as socio-demographic characteristics and personal hygiene [30].Current study was conducted in Tabriz, the largest city in northwest of Iran. According to ZiaeiHezarjaribiet al systematic review and meta-analysis study, trichomoniasis is more common in Central provinces of Iran and the minimum rate belongs to the eastern provinces and the mean prevalence rate in other geographical regions was 6.9, 6.7% in West, North respectively.…”
Section: Discussionsupporting
confidence: 91%
“…In present study, of 448 cases, 48 (10.7%) were positive by wet-mount staining examinations and 4 (0.89%) by PCR test (Table1). In the study conducted by Haghighi et al in Zahedan, therate of infection was determined to be 23.3% (21/90) based on wet mount microscopy [10]. The result of study conducted by Ambrozioet al in Brazil showed that 9% of patient were positive for T. vaginalis infection as diagnosed through the direct fresh examination [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation